Effect of water stress on the agronomic, technological, and physiological parameters of several industrial tomato varieties - Bourouhou, Mourad; Saadia, Hani (Indonesian Journal of Agricultural Research, 2025)
This work consists of comparing 04 varieties of industrial tomatoes, of local origins, grown in dry conditions in order to bring out the best agronomic, technological, and physiological performances in order to cope with colossal imports. The results obtained show that the Rio-Grande variety presents the best agronomic performances, such as the aerial part of the plants, the leaf surface, the number of flowers/plants, and the technological performances such as the Brix and the average weight of the fruits, the Rio-Grande varieties, followed by the Elgon. have the best performance compared to El Karma and Heinz 1350. The study of physiological parameters is carried out according to well-determined protocols, namely chlorophyll A, carotenoids, total proteins, and proline shows that the Rio-Grande variety records the greatest physiological activity, followed by Elgon, among others the Heinz1350 and El Karma varieties, which are the most influenced by lack of water (water stress). Proline shows a significant increase for Heinz 1350 and El Karma tomato plants with 0.67 and 0.56 μg/mg successively, while Rio-Grande records 0.49 μg/mg and therefore the least stressed with respect to the species' reactive oxygen (ROS) and climatic hazards. Our work was validated by statistical analysis.